2015
DOI: 10.1155/2015/401509
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis of Canine Visceral Leishmaniasis Using Mimotope Peptides Selected from Phage Displayed Combinatorial Libraries

Abstract: ELISA and RIFI are currently used for serodiagnosis of canine visceral leishmaniasis (CVL). The accuracy of these tests is controversial in endemic areas where canine infections by Trypanosoma cruzi may occur. We evaluated the usefulness of synthetic peptides that were selected through phage display technique in the serodiagnosis of CVL. Peptides were chosen based on their ability to bind to IgGs purified from infected dogs pooled sera. We selected three phage clones that reacted only with those IgGs. Peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…The use of synthetic peptides [30, 31] as antigens in diagnosis of canine leishmaniasis may limit cross reactivity. It would also circumvent reliance on parasite extracts, which are not easy to reproducibly produce, and thus may help assay standardization.…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic peptides [30, 31] as antigens in diagnosis of canine leishmaniasis may limit cross reactivity. It would also circumvent reliance on parasite extracts, which are not easy to reproducibly produce, and thus may help assay standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that promastigote antigens of Leishmania cross-react with sera showing positive reactions against antigens of malaria and Chagas disease ( Romero et al, 2009 , Pinedo-Cancino et al, 2013 , Toledo-Machado et al, 2015 ). In this study, sera positive for malaria and Chagas disease showed considerable cross reactivity in the p-ELISA while the rK39 ICT and IFAT did not.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited antileishmanial drugs available for treatmenf of VL, effective clinical management depend largely on early and unequivocal diagnosis. However, regarding the diagnosis of human cases, problems of cross-reactivity have also been described in serological tests, especially when it refers to individuals from areas where Chagas’ disease is also present [27]. These data indicate the urgent need to discover new antigens to improve the current serological tests for VL diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, several antigens, as peptides, recombinant proteins and chimeric proteins were obtained to be used in VL and CVL diagnosis [21, 23]. Moreover, identification of reactive peptides on the surface of the phages and integration with immunoinformatics allows their use and/or the subsequent synthetic construction with a directed application for diagnosis [27, 28]. Thus, using the knowledge acquired in immunoinformatics for the discovery of targets for the diagnosis of infectious diseases [27, 2931], and also for the limitations known for the serodiagnosis of VL, the objective to the present study was to identify and validate new antigens of L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation